1962
DOI: 10.33915/agnic.476
|View full text |Cite
|
Sign up to set email alerts
|

Restricted and full-feeding of growing pullets

Abstract: The results of a 12-year study of methods of growing New Hampshire pullets indicate that good pullets may be grown by any of the 1 1 methods studied. The results may be summarized as follows: (1) Range-reared pullets which were limited to a two-hour feeding time for five days per week and a light feeding of grain on the other two days consumed about 15 per cent less feed in 20 weeks than full-fed range-reared pullets consumed in 16 weeks. (2) Sexual maturity of the limited-fed pullets was retarded an average o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1963
1963
1971
1971

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Thus, Temperton and Dudley (1941), Vondell (1943), Heuser, Norris and Bruckner (1945), Novikoff and Biely (1945), Schneider, Bohren and Anderson (1955), Ringrose (1958), Tomhave (1958) and Clark, Bletner and Cunningham (1962) found that saving in total food intake by the birds in their experiments did not exceed 12^ per cent, and delays in sexual maturity were either small or not observed.…”
Section: Restriction By Limiting the Time Of Access To Foodmentioning
confidence: 90%
See 1 more Smart Citation
“…Thus, Temperton and Dudley (1941), Vondell (1943), Heuser, Norris and Bruckner (1945), Novikoff and Biely (1945), Schneider, Bohren and Anderson (1955), Ringrose (1958), Tomhave (1958) and Clark, Bletner and Cunningham (1962) found that saving in total food intake by the birds in their experiments did not exceed 12^ per cent, and delays in sexual maturity were either small or not observed.…”
Section: Restriction By Limiting the Time Of Access To Foodmentioning
confidence: 90%
“…Vondell (1943) found that pullets limited to 15 min grain feeding a day and access to mash for 2 h/d on 6 d in the week ate 29 per cent less and matured 14 d later than fully fed pullets. Heuser et al (1945) and Clark et al (1962) showed that when pullets were allowed access to mash for 2 h/d for 5 d a week, greater savings in food and lone er delays in maturity resulted than when access to food was limited on a daily basis.…”
Section: Restriction By Limiting the Time Of Access To Foodmentioning
confidence: 96%
“…Average egg weights at 350 days of age for all years and locations showed a .3 gm. Some reports (Mac-Intyre and Aitken, 1959;and Clark et al, 1962) obtained an increase in egg weight with feed restriction, while Gowe (1961, 1964) found smaller egg size in one experiment and no difference in another when feed was restricted. The location with the "pure" strains had consistently lower egg weight than the locations with the strain crosses.…”
Section: Ences (Restricted-full-fed) In Several Traits and The Probabmentioning
confidence: 96%